Auditor Independence and Experience in Fraud Detection: the Crucial Role of Professional Skepticism - I Putu Budi ANGGIRIAWAN; Anak Agung Ketut JAYAWARSA (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to examine the effect of auditor independence and experience on fraud detection, with professional skepticism as a moderating variable. In today's business world, many companies strive to achieve maximum profits. In pursuit of this goal, some companies engage in fraudulent practices, which have become common among businesspeople and are well-known to the general public. These fraudulent practices occur not only in the private sector but are also frequently found in the government sector, harming many parties due to inaccurate and irrelevant information. Investors are the most affected, as they often make incorrect investment decisions based on misleading information. Agency theory suggests that more independent auditors tend to be more effective in detecting fraud because they are more likely to act in the interest of the capital owners than less independent auditors. This study involves 108 auditors from 19 audit firms in Bali. The structural equation modeling analysis method was employed to measure the strength of the relationship between the dependent and independent variables using Smart PLS. The results show that auditor independence and experience have a positive impact on fraud detection, and professional skepticism strengthens the effect of independence and auditor experience on fraud detection.